An ex vivo model to induce early fibrosis-like changes in human precision-cut lung slices - Alsafadi, Hani N.; Staab-Weijnitz, Claudia A.; Lehmann, Mareike; Lindner, Michael; Peschel, Britta; Königshoff, Melanie; Wagner, Darcy E. (American journal of physiology. Lung cellular and molecular physiology, 2017)
Idiopathic pulmonary fibrosis (IPF) is a devastating chronic interstitial lung disease (ILD) characterized by lung tissue scarring and high morbidity. Lung epithelial injury, myofibroblast activation, and deranged repair are believed to be key processes involved in disease onset and progression, but the exact molecular mechanisms behind IPF remain unclear. Several drugs have been shown to slow disease progression, but treatments that halt or reverse IPF progression have not been identified. Ex vivo models of human lung have been proposed for drug discovery, one of which is precision-cut lung slices (PCLS). Although PCLS production from IPF explants is possible, IPF explants are rare and typically represent end-stage disease. Here we present a novel model of early fibrosis-like changes in human PCLS derived from patients without ILD/IPF using a combination of profibrotic growth factors and signaling molecules (transforming growth factor-β, tumor necrosis factor-α, platelet-derived growth factor-AB, and lysophosphatidic acid). Fibrotic-like changes of PCLS were qualitatively analyzed by histology and immunofluorescence and quantitatively by water-soluble tetrazolium-1, RT-qPCR, Western blot analysis, and ELISA. PCLS remained viable after 5 days of treatment, and fibrotic gene expression ( FN1, SERPINE1, COL1A1, CTGF, MMP7, and ACTA2) increased as early as 24 h of treatment, with increases in protein levels at 48 h and increased deposition of extracellular matrix. Alveolar epithelium reprogramming was evident by decreases in surfactant protein C and loss of HOPX. In summary, using human-derived PCLS, we established a novel ex vivo model that displays characteristics of early fibrosis and could be used to evaluate novel therapies and study early-stage IPF pathomechanisms.